Developing Students’ Writing Skill on Narrative Text Using Guided Composition Technique (GCT): An Action Research - Sri Syuryatul Afifah; Hasti Robiasih (Universitas Sarjanawiyata Tamansiswa, 2018)
The study aims to describe the development of the students’ writing skill through the implementation of Guided Composition Technique (GCT) learning approach. This research is a Classroom Action Research consisting of three cycles. The subject of this research was 31 eighth grade students of SMPN 1 Borobudur of the academic year 2013/2014. The data were collected from the result of group task, observation, analysis of students’ work and interview. The obtained data were analyzed qualitatively in three steps of data reduction, data display and conclusion drawing. The results that there were many problems faced by the students in developing their writing skill which can be classified into five aspects: grammar, punctuation, vocabulary, organization and content. The implementation of GCT learning technique could develop their writing skill. It was found that the average score gained by the students using guided words or phrases constructions was 70.06, guided questions was 75.90, and guided picture was 76.26.The guided picture was the favourite one. On the students’ motivation in learning English, there was improvement from cycle to cycle. In the first cycle there were 63.55% students having good motivation. Whereas the second and third cycle, there were 74.52% and 90% students getting good motivation. Between 250-300 words; must focus on: aims of the study, methods, findings, conclusions, and implications.